The Strategies to Improve Customer Experience: A Case of Online Shopping Platform - Wan Amiera Wan Jusoh; Nor Irvoni Mohd Ishar; Muhammad Ilham Sjahrir; Nur Fatihah Shuhada Hussin (Universitas Airlangga, 2022)
Background: As the e-commerce industry has been growing recently, it is crucial to examine the factors of customer experience towards online shopping platforms. In this study, researchers aim to examine the influence of website design, website security, and customer service towards customer experience that has led to the preference of online shopping platform in Malaysia. Purpose: The first objective of this study is to analyze the current situation of customer experience with the preferred online shopping platform among university students. Secondly, this study aims to examine the influence of website design, website security, and customer service towards customer experience. As for the third objective, this study aims to recommend strategies to improve customer experience with the online shopping platform among university students. Design/Methodology/Approach: A total of 266 respondents have participated in this study. However, 83 respondents have no experience in using the online shopping platform (OSP), hence they did not fulfill the requirement. Therefore, only 183 sets of questionnaires were analyzed for the study. Finding: The result shows that there are three factors: website design, website security and customer service identified to significantly influence customer experience. Research Limitation: To understand customer online shopping experience, this study focuses at three factors: the website design, website security and customer service. Whilst the unit of analysis is only limited to university students as the respondents. Originality/Value: The value of this study is researchers have examined the factors that influenced customer online experience and provide recommendations with nine strategies for online shopping platform to improve their customers' online experience. The strategies are known as best-cost strategies, innovation strategies (live-streaming), improve website design features, improve website security, improve customer service KPIs, vertical integration strategies, non-equity strategic alliance, offensive strategies, and outsourcing strategies. Keywords: customer online experience, website design, website security, customer service, Malaysia.